Identification of metabolites of Radix Paeoniae Alba extract in rat bile, plasma and urine by ultra-performance liquid chromatographyâquadrupole time-of-flight mass spectrometry - Zheng-Wei Chen; Ling Tong; Shu-Ming Li; Dong-Xiang Li; Ying Zhang; Shui-Ping Zhou; Yong-Hong Zhu; He Sun (Elsevier, 2014)
Ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLCâQ-TOF/MS) was developed to identify the absorbed parent components and metabolites in rat bile, plasma and urine after oral administration of Radix Paeoniae Alba extract (RPAE). A total of 65 compounds were detected in rat bile, plasma and urine samples, including 11 parent compounds and 54 metabolites. The results indicated that glucuronidation, hydroxylation and methylation were the major metabolic pathways of the components of RPAE. Furthermore, the results of this work demonstrated that UPLCâQ-TOF/MS combined with MetaboLynxâ¢ software and mass defect filtering (MDF) could provide unique high throughput capabilities for drug metabolism study, with excellent MS mass accuracy and enhanced MSE data acquisition. With the MSE technique, both precursor and fragment mass spectra can be simultaneously acquired by alternating between high and low collision energy during a single chromatographic run. Keywords: Radix Paeoniae Alba, Metabolite profiling, UPLCâQ-TOF/MS, Monoterpene glycosides